Comparison of the Effectiveness Between Surgical Therapy and Conservative Therapy in the Management of Tuberculosis Spondylitis: A Comprehensive Systematic Review and Meta-Analysis - Ricky Ananta Herryadi, Gede; Djie To Rante, Su; Oka Mahendra, I Made (Syntax Corporation Indonesia, 2025)
Spinal tuberculosis (TB) is the most common form of skeletal TB, with the thoracolumbar junction being the most frequently affected region, while cervical spine TB remains relatively rare, accounting for only 3% to 5% of cases. Historically, non-operative treatment was the only option in the pre-antibiotic era. However, with the introduction of effective combination chemotherapy in the early 1950s, the mortality rate for spinal TB significantly decreased to 1%–3%. Despite advancements in medical therapy, surgical intervention remains crucial in cases involving neurological complications and kyphosis prevention, with instrumentation playing an integral role in managing spinal pathologies. This study aims to evaluate the effectiveness of surgical therapy versus conservative therapy in the management of tuberculosis spondylitis through a systematic review and meta-analysis following PRISMA guidelines and the PICO format. The research includes randomized controlled trials (RCTs), observational, quasi-experimental, and case-control studies, while studies not directly assessing treatment effectiveness were excluded. A comprehensive literature search using PubMed, Sage Journal, The Lancet, and ScienceDirect initially retrieved 1,499 publications. Through a rigorous three-stage screening process, only 10 articles published between 2014 and 2024 were selected for final analysis. The findings indicate that both conservative anti-TB drug therapy and surgical treatment are safe and effective, particularly for early-diagnosed patients with fewer affected vertebrae. Conservative therapy provides good clinical and radiological outcomes, while surgical intervention offers advantages such as thorough debridement, spinal cord decompression, and improved spinal stabilization. The implications of this study suggest that treatment selection should be tailored based on disease severity and patient-specific conditions. Further research should focus on long-term comparative studies, minimally invasive surgical techniques, and biomechanical modeling to optimize treatment strategies for spinal TB..